PERCUTANEOUS CYSTOLITHOLAPAXY AS AN ALTERNATIVE APPROACH FOR GIANT BLADDER STONES: A CASE SERIES OF PATIENTS WITH SIGNIFICANT COMORBIDITIES - Prasetya Adhyatma, Kharisma; Febrian Prapiska, Fauriski (Indonesian Urological Association, 2022)
Objective: We reported two giant bladder stones cases, with significant comorbidities and mentally impaired patients, treated with PCCL. Case(s) Presentation: We report two cases of giant cystolithiasis (sized 8.8 cm x 7.2 cm and 7.0 cm x 5.8 cm) in male patients with impaired renal functions and mental illness. We performed PCCL on both patients with cystoscopy-guided bladder puncture and dilation, under spinal anesthesia. Stone fragmentation through transurethral (pneumatic) and percutaneous (suprapubic amplatz ultrasound) lithotriptors was performed simultaneously. Discussion: Stone fragments were evacuated through the nephroscope. These fluoroscopy-free procedures were performed under one hour. The patients were discharged on day three post-operatively without indwelling catheter. Conclusion: We performed PCCL with simultaneous transurethral fragmentation in giant bladder stone cases presenting with impaired renal functions and mental illness. We faced no significant post-operative issue. This technique, or its modified approach, is safe and applicable